ANALISIS PENGARUH PENGGUNAAN PEMBELAJARAN MULTIMEDIA TERHADAP MOTIVASI BELAJAR MENULIS ARGUMENTASI PADA SISWA KELAS V SD NEGERI 101902 LUBUK PAKAM TAHUN PEMBELAJARAN 2024-2025 - Sonny Elitha Munthe; Risnawaty; Sutikno; Rahmat Kartolo; Erlinda Nofasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the effect of the use of interactive multimedia on the motivation to learn argumentative writing of fifth grade students at SD Negeri 101902 Lubuk Pakam in the 2024-2025 Academic Year. The research method used is a total sample involving all fifth grade students totaling 38 students. Data collection was carried out through test and observation techniques to measure learning motivation before and after the application of multimedia. The results of data analysis showed a significant increase in student learning motivation, with an average motivation value before the use of multimedia of 65 and increasing to 80 after implementation. Hypothesis testing showed a t-count of 5.67, which was greater than the t-table of 2.00, indicating a significant positive effect of the use of multimedia on student learning motivation. Factors that contribute to increased motivation include active student involvement, variations in media used in learning, and increased understanding of the material. This study concludes that the application of interactive multimedia is effective in increasing students' motivation to learn argumentative writing, thus providing positive implications for the learning process in schools.